Early Class III treatment with Hybrid-Hyrax -Facemask in comparison to Hybrid-Hyrax-Mentoplate - skeletal and dental outcomes - Jan H. Willmann; Manuel Nienkemper; Nour Eldin Tarraf; Benedict Wilmes; Dieter Drescher (SpringerOpen, 2018)
Abstract Background Protraction of maxilla is usually the preferred and more commonly used treatment approach for skeletal Class III with a retrognathic maxilla. The aim of this study was the comparison of the skeletal and dental effects of two skeletally borne appliances for maxillary protraction: a) Hybrid-Hyrax in combination with facemask (FM), b) Hybrid-Hyrax in combination with Mentoplate (ME). Methods Thirty four Patients (17 facemask, 17 Mentoplate) were investigated by means of pre- and posttreatment cephalograms. The two groups matched with regard to treatment time, age gender and type of dentoskeletal deformity before treatment. Results Both groups showed a significant forward movement of A-point (FM GROUP: SNA + 2.23° ± 1.30°- p 0.000*; ME: 2.23° ± 1.43°- p 0.000*). B-Point showed a larger sagittal change in the FM Group (SNB 1.51° ± 1.1°- p 0.000*) compared to the ME group (SNB: − 0.30° ± 0.9°- p 0.070). The FM group showed a significant increase of the ML-NL + 1.86° ± 1.65° (p 0.000*) and NSL-ML + 1.17° ± 1.48 (p 0.006*). Upper Incisor inclination did not change significantly during treatment in both groups as well as the distance of the first upper Molar in relation to A-point. Conclusion Both treatments achieve comparable rates of maxillary protraction, without dentoalveolar side effects. Skeletal anchorage with symphysial plates in the mandible provides greater vertical control and might be the treatment of choice in high angle patients.